2009
DOI: 10.1074/jbc.m109.007807
|View full text |Cite
|
Sign up to set email alerts
|

Critical Factors Determining Dimerization of Human Antizyme Inhibitor

Abstract: Ornithine decarboxylase (ODC) is the first enzyme involved in polyamine biosynthesis, and it catalyzes the decarboxylation of ornithine to putrescine. ODC is a dimeric enzyme, whereas antizyme inhibitor (AZI), a positive regulator of ODC that is homologous to ODC, exists predominantly as a monomer and lacks decarboxylase activity. The goal of this paper was to identify the essential amino acid residues that determine the dimerization of AZI. The nonconserved amino acid residues in the putative dimer interface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 62 publications
0
43
0
Order By: Relevance
“…So far, OAZs are the only proteins described that physically interact with ODC, thereby regulating its enzymatic activity 24; 25; 26 . Under physiological conditions, ODC functions as a homodimer which generates two active sites at the dimer interface that contain residues contributed by each subunit 27 . ODC cycles between monomeric and dimeric forms and ODC activity resides exclusively in the dimeric form.…”
Section: Introductionmentioning
confidence: 99%
“…So far, OAZs are the only proteins described that physically interact with ODC, thereby regulating its enzymatic activity 24; 25; 26 . Under physiological conditions, ODC functions as a homodimer which generates two active sites at the dimer interface that contain residues contributed by each subunit 27 . ODC cycles between monomeric and dimeric forms and ODC activity resides exclusively in the dimeric form.…”
Section: Introductionmentioning
confidence: 99%
“…This study revealed that the goose Azin1 protein had a molecular mass of 50 kDa, and a theoretical pI of 4.79, similar to that of mammals (Murakami et al, 1996;Liu et al, 2011). A previous study showed that the human AZIN1 gene encodes 448 amino acids (Su et al, 2009), while the goose AZIN1 encodes 450 amino acids. The predictive Azin1 amino acid sequence showed that two amino acid deletions had occurred in the domain of pyridoxal-dependent decarboxylase in the human Azin1 protein.…”
Section: Discussionmentioning
confidence: 65%
“…In weak basic solutions, low-level CO 2 exists primarily as bicarbonate (HCO 3 - ). The PEPC-MDH method was widely used for detecting CO 2 produced by decarboxylases (ODC, for example)119202132343536373839. In this method, the first step, catalyzed by Phosphoenolpyruvate Decarboxylase (PEPC), is the bicarbonate condenses with phosphoenol pyruvate to form oxalate, and in the second step, oxalate is enzymatically reduced by Malate Dehydrogenase (MDH, using an NADH cofactor) to form malate and NAD + .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Smithson et al 1 presented an optimized protocol based on this method for screening inhibitors of decarboxylases in the polyamine pathway, and they still used ODC as an example, although the authors claimed that it should be suitable for AdoMetDC too. This is quite surprising to us, since the PEPC-MDH method has actually been used on ODC in many previous studies32373839. Therefore, we supposed that some conditions could have hampered the use of this method in assessing AdoMetDC activity.…”
Section: Discussionmentioning
confidence: 96%